Effects of wheat kernel germination time and drying temperature on compositional and end-use properties of the resulting whole wheat flour. (March 2019) - Poudel, Rachana; Finnie, Sean; Rose, Devin J.
Abstract: The compositional [phytic acid, thiamine, lysine, asparagine, and γ-aminobutyric acid (GABA)] and dough mixing properties, including dough strength and mixing time, and lipolytic activities, including lipase, esterase, and lipoxygenase, were quantified in whole wheat flour obtained from wheat kernels that had been germinated for 24 h, 48 h, or 72 h and dried at either 40 °C or 60 °C. The phytic acid, thiamine, and dough strength of whole grain flour from germinated wheat decreased, whereas lysine, asparagine, GABA, lipase, esterase, and lipoxygenase activities increased compared with flour from ungerminated wheat. Mixing time was not affected by germination time. A small but significant effect of drying temperature was observed for asparagine, GABA, dough strength, and lipase and esterase activities. Drying temperature did not show any differences when the grains were germinated for up to 48 h. Whole grain flour from germinated wheat was added to ungerminated whole wheat flour at 2, 5, and 10% (flour basis). Doughs and breads made from these composite flours had improved mixing properties, loaf volume, and firmness, except at the highest proportions and from longer germination times. This study may provide important information to the food industry when formulating germinated, grain-based products. Highlights: Phytic acid, thiamine, and dough strength decreased due to grain germination. Lysine, asparagine, and γ-aminobutyric acid increased due to grain germination. Lipase, esterase, and lipoxygenase activities increased due to grain germination. Germination time had a greater effect on composition than lot or drying temperature. Small proportion of germinated flour improved quality of whole wheat flour.